Butterfly Pea (Clitoria ternatea L.: Fabaceae) and Its Morphological Variations in Bali - I Wayan Suarna; I Made Saka Wijaya (Universitas Gadjah Mada, 2021)
Butterfly pea (Clitoria ternatea L.) is an important perennial herbaceous plant with a range of uses as ornamental plants, fodder crops, medicine, and sources of natural food colorant and antioxidants. The leaves and pods are commonly used as a source of protein in fodder, while the flowers are usually dried and processed as a high antioxidant-containing tea. The blue variant of butterfly pea was the most commonly used variety, although there are quite diverse butterfly pea varieties. The present study aimed to observe the morphological variations among the 26 butterfly pea accessions that originated from a wide range of areas in Bali. The explorative method was used to obtain diverse specimens (accessions) of butterfly pea in Bali, and subsequently, morphological characterization of the accessions was performed. The primary data of morphological traits that were recorded included stems, leaves, flower structures, flower colors, pods, and seeds. The data were analyzed descriptively to determine the morphological variations between accessions. The results showed three major morphological variations: (i) the colour of the flower (corolla), (ii) the corolla structure, and (iii) the stamen structure. The colour of corolla has four variations: white, mauve, light blue, and dark blue; while the corolla structure has two variations: normal and multiple layered corollas. The stamen character showed a correlation with the structure of the corolla. The normal corolla has diadelphous stamens, while the multiple layered corollas have solitary stamens. These morphological variations are the genetic richness of Indonesia’s biodiversity and should be protected and conserved.